An examination of the effectiveness of test-of-controls audit procedures for detecting fraud. (1st January 2014) - Young, Randall; Moyes, Glen D.
Auditing standards require the internal auditor to consider the risk of fraud as part of the audit engagement. The purpose of this study is to evaluate the internal auditor's perceptions concerning the fraud-detection effectiveness of test-of-control audit procedures within four major accounting cycles. Survey instrument was disseminated to members of the Institute of Internal Auditors. The findings show internal auditors perceive testing for controls concerned with: 1) segregation of duties; 2) restricting access to cash, employee master and payroll data and inventory; 3) bank reconciliations to be effective for detecting fraud. The findings also show that internal auditors perceive testing for adequacy of chart of accounts and discussions with management about their responsibilities within the accounting cycles is not effective for detecting fraud.